PERUBAHAN IKLIM DAN PEMANASAN GLOBAL DI INDONESIA; DAMPAKNYA TERHADAP KONDISI BAWAH PERMUKAAN Studi Kasus : DKI JAKARTA - Rachmat Fajar Lubis; Robert Delinom (Pusbindiklat - LIPI, 2010)
Indonesia is exposed to climate change, especially with regard to the rising sea level, changes in precipitation and extreme events. This will particularly impact to many sectors in this country. In order to evaluate the impact on subsurface environment, groundwater temperatures in boreholes can be an important source of information on recent climatic changes. Subsurface temperatures in Jakarta city were analyzed to evaluate the effects. As a result the magnitude of surface warming was increase 1.4°C which agreed with the increase of air temperature meteorological data during the last 100 years. This is the preliminary results of significant increase in climate change during the last century in Jakarta. Still today, the information on vulnerability and adaptive measures is not sufficient in order to plan and design appropriate activities on the national level in Indonesia.